The effect of electric shock in the stimulation of splits of cellular plant cells derived from the calas of the undergrowth of the plants of the sun flower and planted in multiple drops of oxides - Jamela Rasheed; Wjdan Qasem (College of Education for Pure Sciences, 2005)
Sunflower friable callus used in obtaining cell suspension culture in liquid MS medium containing 2,0 mg /L.NAA and 1.0 mg/ L BA, The cell started their first division after 24hours and continued their division reaching to 7,33-8.50 x 103 cell / ml after 4 days of incubation. Culturing of cell suspension using Multiple Drop Array (MDA) technique promote the divisions of cells and the formation of cell colonies which developed to form callus primordia, Electro treatment of cell suspension enhanced division of cells, and the first division, occurs during 3-5 days the. total number of cells colonies reach to 380. Callus formed cell suspension from sunflower did not overcome the regeneration problem in this plant,